2021
DOI: 10.20473/mgk.v10i2.2021.187-195
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Adiksi Internet dengan Status Gizi pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Airlangga

Abstract: ABSTRAK:Latar Belakang: Penggunaan Internet yang berlebihan saat ini menyebabkan masalah yang disebut Internet Addiction Disorder (IAD) atau kecanduan internet. Adiksi internet adalah seseorang yang tidak mampu mengontrol diri untuk menggunakan internet, yang dapat menyebabkan gangguan kesehatan fisik, psikis, maupun kemampuan sosialisasi, dam perubahan pola makan yang mengakibatkan berubahan status gizi. Akses internet yang mudah merupakan faktor utama dalam kecanduan internet dan dapat mengubah gaya hidup. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
1
0
3
Order By: Relevance
“…The results of Jamni's research (2020) revealed that the use of gadgets in adolescents is still very high and is followed by a need for appropriate eating patterns. In line with the results of the study by Kurniawan and Farapti (2021), excessive use of smartphones is a high risk of having irregular eating patterns because they lose their appetite, often skip dinner, and choose to consume snacks that tend to have high energy which will undoubtedly have an impact on increasing the prevalence of obesity in adolescents. The findings of Domoff et al (2020) showed that addictive cell phone use in adolescents could increase the risk of obesogenic or high-calorie eating behaviors, disordered eating, overeating, food addiction, and a higher body fat percentage.…”
Section: Introductionsupporting
confidence: 66%
“…The results of Jamni's research (2020) revealed that the use of gadgets in adolescents is still very high and is followed by a need for appropriate eating patterns. In line with the results of the study by Kurniawan and Farapti (2021), excessive use of smartphones is a high risk of having irregular eating patterns because they lose their appetite, often skip dinner, and choose to consume snacks that tend to have high energy which will undoubtedly have an impact on increasing the prevalence of obesity in adolescents. The findings of Domoff et al (2020) showed that addictive cell phone use in adolescents could increase the risk of obesogenic or high-calorie eating behaviors, disordered eating, overeating, food addiction, and a higher body fat percentage.…”
Section: Introductionsupporting
confidence: 66%
“…As a recommendation for researchers to further study, examine the influence of other variables such as age, gender, and background on the relationship between fitness, nutritional status, and learning outcomes and conduct a study of fitness and nutritional status on the learning outcomes of physical education students over a longer time (Kurniawan & Farapti, 2021). Then examine the psychological impact of fitness and good nutritional status, such as increasing self-confidence and motivation, on learning outcomes (Lolowang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Data primer dalam penelitian ini didapatkan dengan melakukan observasi gambaran body image yang dialami dengan menggunakan kuesioner secara langsung kepada responden. Dengan kuesioner MBSRQ-AS yang diadopsi dari penelitian Kurniawan, M (2014).…”
Section: Metodeunclassified